ANALISIS KELAYAKAN FINANSIAL LADA PUTIH Di KABUPATEN BANGKA - TJETJEP NURASA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
This study was implemented in 2002 in Bangka Regency as central production ofmuntok pepper, was chosen as a research location. The objectives of study were: ( i)toanalyze the financial visibility of pepper farm, (ii)to identify the channel of white peppermarketing and its margin in each agent of marketing, and ( iii)to analyze the comparativeand competitive advantages of white pepper. Research used the method of structuredsurvey. Primary data were collected from 60 farmers, 15 merchants, 5 agents ofprocessing, and exporters. While secondary data were collected from Central Agency ofStatistics, the Office of Estate Crops, and Institutions of Research related to this study.The financial visibility of pepper farm was counted by using method of input-outputanalysis to get value of Beneficial Cost Ratio (B/C Ratio), Net Present Value ( NPV), andInternal Rate Of Return (IRR). While the value of comparative and competitiveadvantages were estimated by using method of Policy Analysis Matrix ( PAM). Resultsshowed that, period of pepper farm was 7 years where in the fourth year, pepper cropstarted create production of Rp.15.116 million and earnings of Rp.9.4. In fourth year, itgave the highest production and earnings, namely Rp.21.511 million and Rp.12.9 million,respectively. While in the seventh year, it reached the lower production of Rp.8.960million and earnings of Rp.5.620 million/ha/year. At interest rate of 24 percent, it tookNPV of Rp.4.12 million per hectare with B/C Ratio of 1.23. At level of input-output actual,break-even point of pepper farm reached IRR of 32,49 percent. Eighty percent of farmerssold their white pepper to small collecting merchant and the others (70%) sold to largecollecting merchant. The small collecting merchant (80%) sold white pepper to largecollecting merchant and then large collecting merchant sold them to largemerchant/exporter. The highest profit margin successively happened at large collectingmerchant (Rp.680), large merchant/ exporter (Rp.1.600), and small collecting merchant(Rp.565)/kg pepper seed. The highest value of DRCR was happened in the fourth year,namely 0.18. While in three and sixth year, it reached DRCR of 0.25 and 0.34,respectively. At the other side, the value of competitive advantage also saw adequately,that was 0.36 (in three year), 0.38 ( in fourth year), and 0.26 ( in sixth year).